Landslides and the evolution of El Hierro in the Canary Islands - Gee, M; Watts, A; Masson, D; Mitchell, N (2001)
Seismic and sonar data have been used to evaluate the extent and characteristics of giant landslides on the flanks of El Hierro in the Canary Islands. As the youngest and most southwesterly of the Canary Islands, El Hierro has experienced rapid growth and destructive events in its 1.12 million year history. At least four giant landslides (El Golfo, El Julan, San Andres, and Las Playas) have modified ∼450 km3 of El Hierro during the last 200-300 thousand years, with each landslide event removing around 3% of the total edifice volume. The extent of landsliding indicates that it is the main process of decay. We characterise flank morphology around El Hierro and distinguish between rugged, unfailed flank, failed flank and steep gullied ridge. Flanks affected by landsliding have downslope long profiles with distinctive b coefficients and exponential forms. The El Golfo landslide is the most recent (15 ka), best described and clearly defined landslide in the Canary Islands. The El Julan landslide (SW flank) has an estimated volume of 130 km3, an age of >200 ka and is characterised by gravitational slumping. On the SE flank, two new landslide events are reported. The younger landslide (Las Playas) occurred 145-176 ka, has a narrow, steep-sided embayment and a corresponding blocky debris avalanche deposit. The older landslide (San Andres) is recognised on the basis of a highly chaotic seismic facies offshore and reduced upper flank gradients. Its lack of an upper flank embayment and offshore blocky debris avalanche lead us to interpret that the landslide involved gravitational slumping, possibly a series of events, which reduced upper flank gradients, but did not catastrophically collapse to produce a debris avalanche. © 2001 Elsevier Science B.V. All rights reserved.